DAX-1 (NR0B1) and steroidogenic factor-1 (SF-1, NR5A1) in human disease. Issue 4 (August 2015) - Suntharalingham, Jenifer P.; Buonocore, Federica; Duncan, Andrew J.; Achermann, John C.
<x xml:space="preserve">Abstract</x> DAX-1 (NR0B1) and SF-1 (NR5A1) are two nuclear receptor transcription factors that play a key role in human adrenal and reproductive development. Loss of DAX-1 function is classically associated with X-linked adrenal hypoplasia congenita. This condition typically affects boys and presents as primary adrenal insufficiency in early infancy or childhood, hypogonadotropic hypogonadism at puberty and impaired spermatogenesis. Late onset forms of this condition and variant phenotypes are increasingly recognized. In contrast, disruption of SF-1 only rarely causes adrenal insufficiency, usually in combination with testicular dysgenesis. Variants in SF-1/NR5A1 more commonly cause a spectrum of reproductive phenotypes ranging from 46, XY DSD (partial testicular dysgenesis or reduced androgen production) and hypospadias to male factor infertility or primary ovarian insufficiency. Making a specific diagnosis of DAX-1 or SF-1 associated conditions is important for long-term monitoring of endocrine and reproductive function, appropriate genetic counselling for family members, and for providing appropriate informed support for young people.